CTSA : Concurrent Tuple Set Architecture Extending Concurrency to Call Level Interfaces - Pereira, Óscar Mortágua (2013)
Call Level Interfaces (CLI) provide a set of functionalities to ease the connection between client applications and relational databases. Among them, the management of data retrieved from databases is emphasized. The retrieved data is kept in local memory structures (LMS) that allow client applications to read it and modify it through protocols. They are row (tuple) oriented and, while being executed, they cannot be preempted to start another protocol. This restriction leads to several difficulties when applications need to deal with several tuples at a time, namely in concurrent environments where several threads need to access to the same LMS instance, each one pointing to a different tuple and executing its particular protocol. To overcome this drawback, a Concurrent Tuple Set Architecture (CTSA) is proposed for LMS. A performance assessment is also carried out. The outcome is the evidence that in concurrent environments, the CTSA significantly improve the overall performance.